Pengaruh Beban Kerja, Stres Kerja, dan Lingkungan Kerja Terhadap Turnover Intention Pada Generasi Z di Jabodetabek - W, Windayanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the effect of workload, work stress, and work environment on turnover in Generation Z in the Jabodetabek area. Generation Z, known as the generation that grew up with technology, has different characteristics and work preferences compared to previous generations. With a quantitative method, data was collected through a questionnaire distributed to 98 respondents working in various industrial sectors in Jabodetabek. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique operated through SmartPLS 3.0. The results of the analysis show that Workload has a positive and significant effect on Turnover Intention in Generation Z in Jabodetabek. Work stress has a positive and significant effect on Turnover Intention in Generation Z in Jabodetabek. Work stress. Work Environment has a positive and significant effect on Turnover Intention in Generation Z in Jabodetabek.